The Effect of Mesenchymal Secretome Stem Cell Therapy toward Caspase-3 Expression in Pregnant Mice with Pristan-Induced Lupus Model - Adiyana, Febrian Andhika; Bachnas, M Adrianes; Sulistyowati, Sri; Anggraini, Nutria Widya Purna; Respati, Supriyadi Hari (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Systemic lupus erythematosus (SLE) is one of the pregnancy complications which cause an increase in fetal and maternal complications which are mainly caused by placental damage due to chronic inflammation and apoptosis. The rate of apoptosis can be assessed by the high expression of caspase-3 which is the majorexecutioner caspases of apoptosis. The use of Mesenchymal Secretome Stem Cell for SLE therapy has an anti-inflammatory and anti-apoptotic role. This study aimed to examine the effect of mesenchymal secretome stem cell therapy toward caspase-3 expression in pregnant mice with pristan-induced lupus model.Subjects and Method: This study was a randomized controlled trial. This study was conducted at the Prodia ProStem Laboratory, Laboratory of the Faculty of Veterinary Medicine of Airlangga University, and Anatomical Pathology Laboratory, Faculty of Medicine, Airlangga University. A total of 14 healthy BALB/C female mice strain aged 6-8 weeks, with a bodyweight of 20-30 grams, were divided into two groups, (1) 7 pregnant mice who received pristan therapy only, and (2) 7 pregnant mice who received pristan therapy and mesenchymal secretome stem cell.The dependent variable was the caspase-3 expression. The independent variable was the administration of mesenchymal secretome stem cell therapy. The caspase-3 expression was measured by an immunoreactive score. The data were analyzed using independent t-test.Results: After giving mesenchymal secretome stem cell therapy, the mean of the caspase-3 expression in the treatment group (Mean=1.86; SD=0.66) was lower than the control group (Mean=3.30; SD = 1.42), with p=0.031.Conclusion: Mesenchymal secretome stem cell therapy is effective for reducing caspase-3 expression in the placenta of pregnant mice with pristan-induced lupus model.Keywords: Caspase-3 expression, lupus, placentaCorrespondence: Febrian Andhika Adiyana. Department of Obstetrics and Gynecology, Faculty of Medicine, Univesitas Sebelas Maret/Moewardi Surakarta, Indonesia. Email: FebrianAndhika@gmail.com. Mobile: 081215897960.Indonesian Journal of Medicine (2020), 05(03): 224-229https://doi.org/10.26911/theijmed.2020.05.03.07